Desenvolvimento de ligas de hardbanding para redução do casing wear nas operações de perfuração de poços de petróleo - Moura, Edja Iandeyara Freitas (2024)
In Brazil, the ninth largest oil producer in the world, with part of this production (78.1% in 2023) coming from the pre-salt, the demand for the development of technologies that meet the challenges of large distances to be drilled in pre-salt wells increased considerably. In this sense, one of the biggest problems encountered in this drilling is the wear that occurs on the internal wall of the metallic tube that covers the oil well and which, in addition to other functions, must guarantee the structural safety of the well. In this work, a reduced-scale testing methodology was developed that enabled the simulation of the wear that occurs on the inner wall of oil wells during the drilling phase. This methodology, based on the API 7CW standard, was validated and tested using imported materials used by oil companies and available on the Brazilian market. The results found from the wear quantification curves throughout the test showed the same behavior as the results found in the full-scale test that follows the API 7CW standard, thus validating the proposed methodology. This methodology proved to be efficient, mainly for ranking materials. This test methodology was used in the development of metallic alloys to be used as hardbanding, which could compete with imported hardbanding alloys. In the study of the development of hardbandings, it was found that two of the four alloys developed performed 38% better than the best imported hardbanding alloy. The developed alloys, named 3 and 4, presented microconstituents that help in the uniform distribution of contact pressure, favoring the reduction wear on the well casing. Furthermore, they have an austenitic matrix which is more toughness, and which helps to reduce wear on both the well casing and the metallic alloy itself. Furthermore, this study provided a testing methodology and possible national materials that can be applied in the industry, showing promise for carrying out further studies and improving the development of hardbanding alloys in Brazil.